1997
DOI: 10.1016/s0014-2999(97)00106-4
|View full text |Cite
|
Sign up to set email alerts
|

Mutational analysis of the putative devazepide binding site of the CCKA receptor

Abstract: Recently a molecular model was proposed lor the binding site of the antagonist 3M -)-/V-(2,3-dihydro-l-mediyl-2-oxo-5~phenyl-l H-1,4-benzodia/epine-3 s I) I // mdole 2-c^'hoxamide (deva/epide) on the cholecystokinin-A (CCK A) receptor (Van der Bent et al., 1994. Drug Design Discov. 12, 129 14X). Fifteen amino acids were identified, including hydrophilic ones such as Seru '\ Asivw and S e r'71\ that might interact with the caihoxamide moiety in deva/epide. To provide mutational evidence for this model, wild-ty… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
14
0

Year Published

1998
1998
2011
2011

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(16 citation statements)
references
References 16 publications
2
14
0
Order By: Relevance
“…In contrast, mutation of an Asn residue of the rat CCK-AR that corresponds to Asn-333 in the human CCK-AR was reported to affect receptor sensitivity to both agonist (CCK) and nonpeptide antagonist (L-364,718). The authors suggested that the observed effects were due to receptor expression default (33). The results from our study confirmed that exchange of Asn-333 for an Ala diminishes receptor expression at the cell surface.…”
Section: Pharmacological and Functional Evidence For An Interaction Bsupporting
confidence: 86%
“…In contrast, mutation of an Asn residue of the rat CCK-AR that corresponds to Asn-333 in the human CCK-AR was reported to affect receptor sensitivity to both agonist (CCK) and nonpeptide antagonist (L-364,718). The authors suggested that the observed effects were due to receptor expression default (33). The results from our study confirmed that exchange of Asn-333 for an Ala diminishes receptor expression at the cell surface.…”
Section: Pharmacological and Functional Evidence For An Interaction Bsupporting
confidence: 86%
“…The right includes the densitometric analysis of data from three independent experiments (means Ϯ S.E.M.). DTVSAEKHLSGT --HQGSDFGP of helices within the lipid bilayer (Smeets et al, 1997). It is possible that Glu or Asp substitution at position 197 altered the amino terminus conformation and interactions with the extracellular loops, thus enhancing access to the nonpeptidyl binding site while simultaneously disrupting critical determinants for peptide binding within the loop domains.…”
Section: Discussionmentioning
confidence: 99%
“…Rather than ruling out such an interaction, these results probably reflect conformational changes that prevent effective spatial approximation of the residues. Experimental evidence for this included the clear allosteric effect of charge reversal in the position of Arg 197 on facilitation of binding of the benzodiazepine antagonist, L-364,718, that binds within the helical bundle in the lipid bilayer (Smeets et al, 1997). These mutants also displayed enhanced sensitivity to trypsin degradation relative to the wild-type receptor.…”
mentioning
confidence: 99%
“…15,16 Its fluorescence characteristics are described in the current work. These data reveal an emission maximum of the receptorbound state of this ligand at 333 nm, when excited by light at 290 nm.…”
Section: Discussionmentioning
confidence: 98%
“…14 One such class of nonpeptidyl ligands is the 1,5-benzodiazepine derivatives, which have been shown to dock within the intramembranous helical bundle domain. 15,16 This domain has been demonstrated to represent an allosteric site of action, which has been shown to be fully distinct from the orthosteric site of action of the natural peptide ligand of this receptor. 17 By definition, allosteric ligands bind to receptor sites that are distinct from the site of binding of the natural orthosteric ligand.…”
Section: Introductionmentioning
confidence: 99%